2017
DOI: 10.1007/s00391-017-1266-7
|View full text |Cite
|
Sign up to set email alerts
|

Access to community care for people with dementia and their informal carers

Abstract: Enhanced cooperation between GPs and other professions might optimize access to formal dementia care. Team-based approaches focusing on dementia care should be developed further. Informal carers should be supported and relieved in their role. Financial barriers remain which should be further investigated and reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…The study indicated that regardless of the health and social care service in the different countries, people living in the mild to moderate phase of dementia receive little attention and interventions. Moreover, another recent study conducted by Bieber et. al (2017) showed that across Europe, informal carers are mainly pro-active in seeking formal care on behalf of people with dementia, while GP are described as the most important profession supporting the access to formal care.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…The study indicated that regardless of the health and social care service in the different countries, people living in the mild to moderate phase of dementia receive little attention and interventions. Moreover, another recent study conducted by Bieber et. al (2017) showed that across Europe, informal carers are mainly pro-active in seeking formal care on behalf of people with dementia, while GP are described as the most important profession supporting the access to formal care.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…As such, opportunities to offer support are especially valuable upon diagnosis. While social support is recognised within the United Kingdom's (UK) local and national policies (Department of Health, ; DHSSPSNI, ), there is sometimes a fragmented approach to dealing with diagnosed individuals’ social needs, with informal carers, rather than professionals, feeling they take the lead (Bieber et al, ). This article's purpose, then, is to investigate experiences of individuals recently diagnosed with dementia in Northern Ireland (NI) regarding how they were signposted on to social support.…”
Section: Introductionmentioning
confidence: 99%
“…This interview study is part of the larger Actifcare study (Kerpershoek et al, ) which comprises of several work packages (see Figure ) in which access to and the use of formal care was explored in eight European countries (the Netherlands (NL), Germany (DE), United Kingdom (UK), Ireland (IE), Sweden (SE), Norway (NO), Portugal (PT), Italy (IT)). A mapping system was used to provide an overview of the structures and services for those with dementia (Bieber et al, ). A range of 29 different services for people with dementia and their carers were identified and compared across the countries (Kerpershoek et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, not all countries have post‐diagnostic pathways. Existing pathways are described in detail in a different Actifcare paper (Bieber et al, ).…”
Section: Introductionmentioning
confidence: 99%